PERAN MOTIVASI KERJA DALAM MEMEDIASI PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DI KEDAI KOPI TKD BALI - Permadi, I Made Billy; Mujiati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
This research was conducted because is a phenomenon occurs at the TKD Bali, there are still employees who have not shown optimal performance and the company does not fulfill its employee compensation. This study aims to analyze the role of work motivation in mediating the effect of compensation on the performance of TKD Bali employees. The number of samples used were 44 employees using a saturated sample. Data collection in this study was carried out by interview, observation and questionnaire methods. The data analysis technique used in this research is Path Analysis and Sobel Test. Based on the results of the analysis it was found that compensation has a positive and significant effect on employee performance. At the TKD Bali, compensation has a positive and significant effect on work motivation. is a mediating variable partially between the influence of compensation on employee performance at the TKD Bali. The results of this study provide practical implications that are expected to be taken into consideration and input for superiors at TKD Bali in improving employee performance by considering compensation and work motivation.